Polymorphisms in FADS1 and FADS2 alter plasma fatty acids and desaturase levels in type 2 diabetic patients with coronary artery disease. Issue 1 (December 2016) - Li, Si-Wei; Wang, Jin; Yang, Ying; Liu, Zhi-Jie; Cheng, Lin; Liu, Huan-Yu; Ma, Pei; Luo, Wan; Liu, Song-Mei
Abstract Background To explore whether plasma fatty acids and SNPs in the fatty acid desaturase (FADS ) gene associated with type 2 diabetes (T2D) and coronary artery disease (CAD). Methods In this cross-sectional study, we utilized gas chromatography–mass spectrometric analysis and the high-resolution melting method to detect plasma fatty acids and SNPs respectively (rs174537G>T, rs174616C>T, rs174460T>C, and rs174450A>C) in 234 T2D, 200 CAD, 185 T2D&CAD patients, and 253 healthy controls. Results We found that T2D&CAD patients had the highest plasma arachidonic acid, dihomo-gamma-linolenic acid and delta-6 desaturase, and the lowest stearic acid, linolenic acid, and saturated fatty acids; plasma eicosapentaenoic acid and docosahexaenoic acid elevated in T2D patients, but significantly reduced in CAD patients. Moreover, T2D patients with rs174537 GG genotype were at risk of developing T2D&CAD (odds ratio (OR) 1.763; 95 % CI 1.143–2.718;p  = 0.010), with elevated plasma LDL-cholesterol, arachidonic acid, and delta-6 desaturase. Conclusions Our results show that SNPs inFADS gene (particularly rs174537) associate with plasma fatty acids and desaturase levels in patients with both T2D and CAD, which maybe increases the risk of CAD in diabetic patients.